Insufficient Level of Physical Activity and Its Effect on Health Costs in Low- and Middle-Income Countries - Liu, Wei; Dostdar-Rozbahani, Abbas; Tadayon-Zadeh, Fahime; Akbarpour-Beni, Mohsen; Pourkiani, Mohammad; Sadat-Razavi, Fatemeh; Barfi, Vahid; Shahedi, Valiollah (Frontiers in Public Health, 2022)
Evidence suggests that mortality attributed to noncommunicable diseases (NCDs) will increase from 38 million in 2012 to 52 million by 2030. The recent epidemiological data show that these diseases are increasing in low- and middle-income countries so that about 80% of all deaths of NCDs occurred in low- and middle-income countries. It has been estimated that an insufficient level of physical activity leads to a large share of the burden of these diseases. Evidence suggests that the rate of insufficient levels of physical activity in low- and middle-income countries has increased over the past 15 years. The authorities and policymakers must be advocated with consistent evidence from low- and middle-income countries on productivity loss and increased healthcare costs due to the absence or insufficient levels of physical activity. It is also necessary to include physical activity across all policies to prevent possible escalation of the economic burden related to physical inactivity in the near future.